Differences in Knowledge Before and After Instructions on Washing Hands During the Covid-19 Pandemic in the Social Services of the Elderly Management Year 2020 - Nur Masdalifah (International Journal of Public Health Excellence (IJPHE), 2022)
COVID-19 or Coronavirus Disease 2019 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 is thought to spread between people through respiratory droplets produced when coughing and splashes from someone who is sneezing and obtained from contaminated surfaces that then accidentally touch someone's face. One of the groups most vulnerable to being infected with COVID-19 is the elderly (elderly) aged 60 years and over. One way to prevent COVID-19 is to wash your hands. Hand washing is an inexpensive and easy routine, is important in infection control procedures, and is the best method of preventing the transmission of microorganisms. This study examines the differences in knowledge before and after counseling about hand washing during the COVID-19 pandemic. The research design is a One-Group Pretest-Posttest Design study. This is a form of Pre-Experimental Design. The population and sample in this study were 30 elderly people. The results of the pre-test get an average value of 2.37 while the results of the post-test get an average value of 9.67. Based on the SPSS test that has been carried out (P = 0.000; = 0.05 ) Ha (alternative hypothesis) is accepted because the p-value is 0.005 so Ho is rejected with a price level of significance (α) = 5% so that the alternative hypothesis is accepted. Thus the conclusion of this study is that there is a difference in knowledge before and after counseling about hand washing during the COVID-19 pandemic at the Pematangsiantar Elderly Social Service.